Challenges in Implementing Digitally and Interculturally Infused Project-Based Learning for EFL Movie Subtitling - Ayu Bandu Retnomurti; Iskandar, Ifan; Dewanti, Ratna (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
The rapid advancement of technology and the growing importance of intercultural skills in EFL education underscore the necessity for instructional methods that authentically infuse these competencies into practical subtitling projects. Yet, EFL subtitling classes in Indonesia often remain dominated by traditional practices, restricting innovation in project-based learning. This study employs a descriptive qualitative method with three aims: to identify instructional hurdles in applying a digitally and interculturally enhanced PjBL model; to examine specific obstacles experienced during classroom implementation; and to analyze strategies lecturers developed to address these barriers. Data were gathered through interviews, classroom observations, and analysis of student work, and validated using triangulation techniques. Findings indicated that while collaborative activities such as group subtitle analysis and organized project presentations facilitated meaningful interaction among students, issues like uneven material distribution limited opportunities for equal participation. Lecturers responded by incorporating structured scaffolding and adjusting schedules to better accommodate learner needs. Despite the infused PjBL framework enhancing learner engagement and promoting critical reflection, persistent organizational and instructional challenges emerged that require targeted solutions. This research offers valuable insights into how project-based subtitling tasks can operationalize digital and intercultural literacies in Indonesian EFL settings, contributing a practical model for contemporary translation education.